PENERAPAN 5R PADA PENGELOLAAN PERPUSTAKAAN DUSUN KETANDAN, DESA MADUREJO, YOGYAKARTA - Kartinasari Ayuhikmatin Sekarjati (LPPM IST AKPRIND Yogyakarta, 2020)
Community service extension program is carried out as one of the mandatoryactivities from the Institute to the community, which has the aim of applying scienceto the community. This counseling was conducted in the Ketandan Hamlet,Madurejo Village. This hamlet was chosen because it has great potential to bedeveloped. The hamlet has several sectors that can be developed, one of which ishuman resources (HR). The problem encountered in the HR sector was that themanager of the Village Library had problems in paying attention and managing thecomposition and neatness of the bookshelves owned by the